인증시험을 통한 위성용 미소 진동 저감 장치 성능 검증 - 조문신(Mun Shin Jo); 박연혁(Yeon Hyeok Park); 오현웅(Hyun Ung Oh) (항공우주시스템공학회지, 2024)
A spaceborne cryogenic cooler is known to undesirable microvibration disturbances during its on-orbit operation, which is one of the main sources that degrades the image quality of an observation satellite with a high resolution. Several types of vibration isolation systems based on passive approaches have been developed for reducing such microvibration of a linear cooler. A dual coil-spring-type passive isolator was developed. To verify its performance and structural characteristics, transmissibility measurement and modal survey were performed with properly designed dummy instead of a cooler. Results were then used as pass/fail criteria before/after each test. To verify structural and thermal stability of the dual coil-spring-type passive isolator for launch and on-orbit environment, vibration (random and sinusoidal) test, shock test, and thermal cycle test were performed successfully. 적외선 카메라를 탑재한 위성체 내부 진동원 중 검출기 냉각기는 고성능 광학 탑재체의 영상 품질을 저하하는 주요 원인이다. 따라서 광학 성능 확보를 위하여 냉각기 진동 저감이 요구된다. 본 논문에서는 2중 코일 스프링을 적용한 미소 진동 저감 장치에 대하여 기술하였다. 장치의 감쇠 성능과 구조 특성은 냉각기 구동 주파수에서의 전달률과 고유진동수 측정을 수행하여 검증되었다. 또한 발사 및 궤도 환경시험을 수행하여 장치의 구조와 열적 안전성을 검증하였다. 이와 같은 일련의 과정을 통하여 미소진동 저감 장치의 설계 유효성을 입증하였다.